RISE: Green polysaccharides for wound healing / Ainul Hafiza A.H - Abdul Hair, Ainul Hafiza (Office of the Deputy Vice-Chancellor (Research & Innovation), 2022)
There is an emerging challenge to source for biocompatible and biodegradable green materials for wound dressing. Rising concern for safety and an increasing need to reduce environmental depletion risk, has urged researchers to seek for a sustainable alternative. A recent wound management system outlined that the wound dressing must be able to cover the skin injury and support as well as accelerate four stages of wound healing mechanism: haemostasis, inflammation, proliferation, and remodelling. To this day, wound dressing covers various therapeutic characteristics, for instance, providing an incessant wet environment to hold adequate moisture, antibacterial properties to reduce infection, excipient for control release of drugs, and permeable to gas exchange. When these properties are achieved, efficient wound dressing can significantly reduce the number of dressings throughout the healing period. Henceforth, a reduced time, cost-effective, and absence of likelihood of a secondary injury upon dressing removal can decrease the sense of pain.